Application of Alvarado scoring system in the diagnosis of acute appendicitis. - Hindosh, Laith. Naif.; Kamal, . Zuhair Bashir; Alnasir, . Mumtaz khider; Hussein, Wisam Abdulateef (AL-Kindy College Medical Journal, 2015)
Background: Acute appendicitis is the most common abdominal surgical emergency. The diagnosis of this condition is still essentially clinical and there is difficulty in the clinical diagnosis, especially among elderly, children and patients with a typical presentation, so early and accurate diagnosis of acute appendicitis is important to avoid its complications.Objectives: To evaluate the degree of accuracy of Alvarado scoring system in the diagnosis of acute appendicitis.Method: Two hundred patients were admitted to the Alkindy Teaching Hospital from January 2011 to april 2014- presented with symptoms and signs suggestive of acute appendicitis. After examination and investigations all patients were given a score according to Alvarado scoring 10 (8 variables) and they were classified accordingly to 6 groups of scores (score 5, score 6, score 7, score 8, score 9 and score 10). All the patients underwent appendectomy and the appendix specimens were sent for histopathological examination and the patients were divided into two groups:1-patients 7 score (164 patients)2-patients <7 score (36 patients)-We calculate the percentage of appendix proved to be inflamed by histopathology in each group of these 6 scoring groups.Results: The patients ages range from (7-64 years).One hundred six patients were male, 94 patients were female with male: female ratio of 1.24:1.Out of 200 patients, 168 patients had inflamed appendix proved by histopathological study, including 93 male and 75 female, while 32 patients have a normal appendix (13 male, 19 female).The Alvarado sensitivity found to be 83%, specificity is 59%, diagnostic accuracy of 85%, positive predictive value of 92% and negative predictive value of 59%.The diagnostic accuracy of the Alvarado score was found to be increased with the increase in the Alvarado score as it was 81% with Alvarado score 7 it was 100% in Alvarado score 10.Conclusion : Alvarado scoring system is a useful tool in diagnosis of acute appendicitis because it is simple, with high diagnostic accuracy rate and this accuracy increase proportionally to the increase in the degree of the score.Alvarado scoring system is a useful tool in diagnosis of acute appendicitis because it is simple, with high diagnostic accuracy rate and this accuracy increase proportionally to the increase in the degree of the score